SHORT-TERM EFFECT OF Naja naja SHED SKIN EXTRACT ON HISTOPATHOLOGY OF TESTIS, EPIDIDYMIS AND VAS DEFERENS OF SWISS ALBINO MICE - GHOSH, RAJARSHI; DAS, SOUBHIK; MITRA, DEEPSHIKHA; BHATTACHARJEE, PRADIP; DASGUPTA, SUBIR CHANDRA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Ancient literature reveals that snake shed skin had been frequently used to treat several diseases like glaucoma, hernia, psoriasis, hemorrhoids, etc. Previously, it was reported that Naja naja shed skin extract causes temporary cessation of the estrous cycle and altered female reproductive hormones in rodents, and the probable bioactive molecule behind such alterations was also identified. Based on this information, the present study was designed to establish the effect of Naja naja shed skin extract on the male reproductive system of Swiss albino mice. The extract was prepared with physiological saline and was injected intraperitoneally in the male mice for 7 consecutive days @ 10 mg kg-1 body weight. The short-term histopathological studies were performed by Haematoxylin and Eosin staining and the sperm morphology was analyzed by using bright-field microscopy. The snake skin extract markedly changed the gross histological architecture of the seminiferous tubules including disorganization of germinal epithelial cells, accumulation of exfoliated cells in the lumen, tailless sperm in the epididymis, disorganized basal cells in vas deferens as well as marked alteration of sperm morphology. The present work with snake shed skin strongly indicates that it is not simply a biological waste, but it might be a treasure house of many bioactive compounds.